Land cover and natural riverscape heterogeneity shape in-stream thermal regimes: Implications for Atlantic salmon (Salmo salar) conservation - Hugo Reis Medeiros; Ben R. Collison; Kevin Ferris; Tim L. Webster; Amy Weston; Edmund A. Halfyard (Science of The Total Environment, 2026)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Modelling the ancient maize agriculture potential of landforms in Tikal National Park, Guatemala - Chris S. Balzotti; David L. Webster; Tim M. Murtha; Steven L. Petersen; Richard L. Burnett; Richard E. Terry (International Journal of Remote Sensing, 2013)

Environmental predictors of global parrot (Aves: Psittaciformes) species richness and phylogenetic diversity - Richard G. Davies; C. David L. Orme; Andrea J. Webster; Kate E. Jones; Tim M. Blackburn; Kevin J. Gaston (Global Ecology and Biogeography, 2007)
Aim Spatial patterns of phylogenetic diversity (PD) aid our ability to discern diversification rate mechanisms underlying hypotheses for the large‐scale distribution of biodiversity. We develop a predictive framework for the way in which spatial patterns of PD vary with those of species richness, depending on the balance between speciation and extinction rates. Within this framework, diversification processes thought to underlie the productive energy, ambient energy, topographic variability and habitat variety hypotheses predict that gradients of increase in species richness will be associated with: (1) decreasing extinction rates where driven by productive energy, hence increasing relative PD (i.e. PD controlling for species richness, or PD rel ); (2) a similar positive relationship between ambient energy and PD rel ; (3) increasing speciation rates where driven by topographic variability, hence decreasing PD rel ; and (4) no consistent relationship between PD rel and habitat variety when driven by the latter. We test these predictions using distributional data on parrots. Location Neotropical, Afrotropical, Indo‐Malayan and Australasian realms. Methods Spatial models were used to test the predictions. Results Globally, a positive association between productive energy and PD rel confirms prediction (1). However, within realms, hump‐shaped relationships suggest the importance of decreasing extinction rates up to a threshold level of productive energy, and the increasing importance of speciation rates thereafter. Ambient energy is positively associated with PD rel in Australasia, Indo‐Malaya, and globally, supporting prediction (2). However, this is driven by the coincidence of highest PD rel in areas of high ambient energy and intermediate productive energy (i.e. in seasonal tropical environments), which may be characterized by relatively low speciation and extinction rates. In the Neotropics, increasing topographic variability is associated with decreasing PD rel and increasing species richness, suggesting an increasing gradient of speciation, supporting prediction (3). Elsewhere, the signal of this mechanism may be obscured by collinearities with energy gradients. The lack of an overall relationship between habitat diversity and PD rel confirms prediction (4). Main conclusions Spatial patterns of PD rel in relation to environmental gradients may be sensitive to collinearities among those gradients. Nevertheless, patterns emerge which have implications for the relative importance of speciation and extinction processes in generating latitudinal diversity gradients.